2021
DOI: 10.3389/feart.2021.604388
|View full text |Cite
|
Sign up to set email alerts
|

Database of Active Faults in Slovenia: Compiling a New Active Fault Database at the Junction Between the Alps, the Dinarides and the Pannonian Basin Tectonic Domains

Abstract: We present the compilation of a new database of active faults in Slovenia, aiming at introducing geological data for the first time as input for a new national seismic hazard model. The area at the junction of the Alps, the Dinarides, and the Pannonian Basin is moderately seismically active. About a dozen Mw > 5.5 earthquakes have occurred across the national territory in the last millennium, four of which in the instrumental era. The relative paucity of major earthquakes and low to moderate fault slip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 76 publications
1
57
1
Order By: Relevance
“…Since the Pliocene, N-S shortening is taken up by right-lateral motion on a NW-SE-trending strike-slip fault system known as the Dinaric Fault System (e.g. Poljak et al, 2000;Vrabec and Fodor, 2006;Placer et al, 2010;Moulin et al, 2016;Atanackov et al, 2021;Figs. 1-3).…”
Section: Geological Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…Since the Pliocene, N-S shortening is taken up by right-lateral motion on a NW-SE-trending strike-slip fault system known as the Dinaric Fault System (e.g. Poljak et al, 2000;Vrabec and Fodor, 2006;Placer et al, 2010;Moulin et al, 2016;Atanackov et al, 2021;Figs. 1-3).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…The first geological evidence for the late Quaternary activity of the Idrija Fault came from faulted fluvial deposits in Kanomlja (Cunningham et al, 2006;Bavec et al, 2012) and in the Učja River valley (Vrabec, 2012). Geomorphological work showed that the fault offsets the regional drainage system and late Qua- Atanackov et al (2021). Historical and instrumental seismicity are from the SHEEC database (Stucchi et al, 2013;Grünthal et al, 2013); the 1511 Idrija earthquake is marked (note that the location is uncertain; the earthquake probably occurred either on the Idrija Fault or on the SW side of the mountain front in Italy).…”
Section: Active Tectonicsmentioning
confidence: 99%
See 3 more Smart Citations